Cyberloafing In The Digital Age, Disrupting Or Enhancing Performance?: Literature Review - Dudija, Nidya; Miranti, Rizka (International Journal of Science, Technology & Management, 2024)
One aspect that becomes a reference for the development of a company is employee performance. In an effort to improve employee performance, several companies implement policies by providing technology benefits such as internet, cellphones and computers. The original aim of implementing this technology allowance was to maximize employee performance. However, the facts on the ground show that there is a phenomenon of irregularities in the use of these technological facilities which are used for personal interests, whether opening e-mail, playing games, accessing personal social media and accessing entertainment sites. This phenomenon is called cyberloafing. Cyberloafing is a serious problem related to employee behavior, where this behavior will be contrary to the employee's integrity in completing their duties. Cyberloafing is disciplinary behavior where a worker diverts concentration and work time to activities outside of work interests. This article reviews the literature on cyberloafing among Generation Z ASN employees to help readers better understand this condition. This aims to clarify the phenomenon of cyberloafing, the impact of cyberloafing, benchmarks and dimensions of cyberloafing.